PENERAPAN MEDIA VIDEO POWTOON UNTUK PEMBELAJARAN PANGKAS RAMBUT MEDIUM HUSH CUT DI SMK NEGERI 6 SURABAYA - Kaleka, Grace; Nia Kusstianti; Dindy Sinta Megasari; Sri Usodoningtyas (Program Studi Pendidikan Tata Rias, 2025)
Current technological developments have a great influence on the creation of learning media that support learning outcomes. One of the influences of technological developments is the existence of learning media in the form of powtoon videos. This powtoon video is an IT-based web application that has image and audio features. This powtoon video learning media is very easy to access by teachers so that it can help create interesting learning for students. This study aims to determine 1) the feasibility of powtoon video media, 2) student learning outcomes and 3) student responses to the application of powtoon videos to medium hush cut hair cutting material at SMK Negeri Surabaya. This study uses a quantitative method with a pre-experimental one shoot case study design, involving 31 grade XI Beauty students. Data were obtained through media validation, learning outcome tests, and student response questionnaires. The validation results showed that powtoon media was very feasible to use with an average of 90.33%. The average student learning outcomes reached 86.38 with 58% in the very good category and 42% in the good category. The students' response to this media was also very positive with a percentage of 97.86%. Thus, the powtoon video media is effective in improving students' understanding and skills in learning hair cutting.